Modeling mexican electricity market: experimental results - Kalashnikov, Vitaly; Kalashnykova, Nataliya I.; Castillo Pérez, Felipe de Jesús (Western Academic Press, 2010)
In this paper, we propose an oligopolistic model of electricity market of Mexico and analyze numerical experiments based upon this model. Presently, the Mexican electricity market is presented by the state-regulated monopoly, so a competition market is not yet established. Our work can be evaluated as an empirical study of possible liberalization effects for Mexico. An oligopolistic market structure emerges from the energy market analysis and is characterized not only by the mutual influence upon prices due to the market shares and power but also by the naturally limited number of operating firms-producers at the market. In this Cournot-Nash model, the electricity firms maximize their profit and enlarge their market shares. For a comparison, we also introduce the notion of perfect competition, where each agent reacts as a price-taker equalizing prices and marginal costs in order to maximize its profit. The computational game theoretic modeling tool, offered in this paper, composed as a mixed complementarity problem (MCP), solved by the GAMS (www.gams.com) algorithm PATH. It was applied to the Mexican electricity market data to obtain Nash equilibrium in the perfect competition and Cournot cases, as well as open market scenario with international trade with the USA.